Teaching it with synthetic communities of practice - Overmyer, S.P.; Ivanov, I.; Fazylova, A.; Islam, S.; Kinayat, K.; Kussainov, K.; Sailuova, N.; Zhunisbekova, I. (Nazarbayev University, 2013)
The goal of this research is to unleash the creative potential of computer science students by engaging them in problem-solving activities within immersive simulations of real-world problem domains. This engagement provides the experience of learning to create solutions to ill-defined, real-world problems in a risk-free, but constrained and adaptive environment. Our long-term intention is to exploit the value of communities of practice for individual students by determining the necessary and sufficient conditions for the formation of synthetic communities of practice (SCoP). This SCoP typically involves one “live” student, and a “community” of intelligent agents.
Keywords: problem-solving activities; synthetic communities of practice; NURIS